LURAP1L-AS1 long noncoding RNA promotes breast cancer progression and associates with poor prognosis - Radhakrishnan Vishnubalaji; Dania Awata; Nehad M. Alajez (Non-coding RNA Research)
Long noncoding RNAs (lncRNAs) are emerging as critical regulators of cancer biology, yet their roles in breast cancer, particularly in triple-negative breast cancer (TNBC), remain incompletely understood. Through a custom siRNA library screen targeting TNBC-associated lncRNAs in MDA-MB-231 and BT-549 TNBC cell models, we identified LURAP1L-AS1 as a key modulator of TNBC progression. Survival analysis of TNBC patients demonstrated a significant association between elevated LURAP1L-AS1 expression and poor clinical outcomes.LURAP1L-AS1 knockdown significantly impaired colony formation and organoid growth of TNBC models, associated with increased apoptosis thus highlighting its role in promoting tumorigenicity. RNA sequencing of LURAP1L-AS1-depleted cells revealed dysregulation of pathways related to cell proliferation, apoptosis, migration, and RNA processing. Bioinformatics analysis predicted LURAP1L-AS1 to function as a competitive endogenous RNA (ceRNA), sponging key microRNAs, such as miR-7a-5p, miR-101-3p, miR-181a-5p, and miR-27a-3p, thereby modulating oncogenes including EZH2, MCL1, and KRAS, which are linked to increased cancer cell survival, proliferation, and metastasis.In addition to its role in TNBC, correlation analysis using breast cancer patient datasets revealed a significant association between LURAP1L-AS1 and ESR1 expression, suggesting its broader impact across breast cancer subtypes. Concordantly, LURAP1L-AS1 depletion inhibited estrogen receptor-positive (ER+) MCF7 breast cancer cells colony formation and organotypic growth.Our findings establish LURAP1L-AS1 as a functional lncRNA that promotes breast cancer progression, highlighting its potential for use in RNA-based therapies for breast cancer.